The Effect of Routine Reversal of Neuromuscular Blockade on Adequacy of Recurrent Laryngeal Nerve Stimulation during Thyroid Surgery. Issue 4 (July 2015) - Marshall, S. D.; Boden, E.; Serpell, J.
Testing of the integrity of the recurrent laryngeal nerve during thyroid surgery has become routine practice for many surgeons to aid dissection and minimise the chance of inadvertent nerve injury. We hypothesised that routine reversal of an intermediate-acting, non-depolarising neuromuscular blocking agent would improve conditions for stimulation of the recurrent laryngeal nerve. We conducted a single-centre, randomised, double-blind placebo-controlled trial of patients undergoing thyroid surgery by the same surgeon. After randomisation, the participants received either neostigmine 2.5 mg with glycopyrrolate 0.4 mg or placebo, at 30 minutes after induction of anaesthesia and administration of 0.4 mg/kg of atracurium. The primary outcome was the subjective assessment by the surgeon as to whether the neuromuscular function was adequate for stimulation of the recurrent laryngeal nerve using a neuromuscular integrity monitor (NIM). Time to NIM stimulation was 44.6 minutes in the placebo group and 41.4 minutes in the intervention group ( P =0.268). Of the 21 patients who received the neuromuscular blockade reversal, 20 (95.2%) had adequate surgical conditions for NIM stimulation, compared to 9 out of 18 patients (50%) in the placebo group ( P =0.002). Three of the ten patients (30%) with inadequate reversal showed no evidence of residual blockade assessed peripherally. The routine reversal of neuromuscular blockade at 30 minutes post induction appears to result in adequate surgical conditions for safe stimulation of the recurrent laryngeal nerve. Return of neuromuscular function at a peripheral site does not guarantee adequate laryngeal muscle function for use of the NIM.